Balancing sustainable development and cultural heritage preservation: Luxury burial legacies in Singapore - OCON, David (Institutional Knowledge at Singapore Management University, 2021)
Singapore tops multiple global rankings for the consumption of luxury products. In this land-scarce and densely-populated city-state, to purchase a high-end car, landed property, or to have a fine dining experience, ranks amongst the most expensive in all Asian cities. That luxurious approach in life, however, does not find a parallel in death. As this paper indicates, a life of luxuries in Singapore does not necessarily mean deluxe burials, graves, mausoleums, or shrines. In fact, due to scarcity of land and the tight control on its usage, there are limited options for the well-off to display the same sense of wealth in death as they did in life. This paper explores the correlation between elaborate burials and the right to eternal rest, and investigates how a land-deprived country faces the challenge of sustainably balancing modernisation aspirations with respect for burial customs and cultural heritage.